البحر الأسود بين السيادة العثمانية والتهديدات الروسية في القرن الثامن عشر - عويد عبد فهد (Journal of College of Education, 2018)
البحر الأسود بين السيادة العثمانية والتهديدات الروسية في القرن الثامن عشر